Kecerdasan Anak Penghafal Al-Qur’an Dalam Mata Pelajaran Pendidikan Agama Islam di SMP Enterpreneur Ar-Ridwan Binangun Wonosobo - Fahmi Nuriyah Tami; Mukromin Mukromin; Faisal Kamal (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This thesis aims to: 1) determine the concept of intelligence in children who memorize the Al-Qur'an and Islamic religious education subjects at Ar-Ridwan Binangun Binangun Wonosobo Entrepreneur Middle School; 2) to determine the intelligence of children who memorize the Al-Qur'an and Islamic religious education subjects at Entrepreneur Ar-Ridwan Binangun Wonosobo Middle School. This thesis uses a research approach using qualitative field research, qualitative field research itself is research that has characteristics, which basically state the actual situation or as it is without changing it into symbols or numbers. The results of the research show that: 1) the intelligence of children who memorize the Koran and those who do not memorize it is different; 2) the inhibiting factors in the intelligence of children memorizing the Koran in Islamic Religious Education subjects have not yet been resolved and the supporting factors that make it easier for children to memorize also require different handling; 3) students' responses in dealing with their respective intelligence problems are by synergizing with teaching staff to become a unified whole in the learning process.